Konstruksi Nilai Sejarah Melalui Ritual Adat Tatera Karau: Studi Etnografi Masyarakat Kobalima Timur, Pulau Timor - Moses Kollo; Melkianus Pote Hadi (Jurnal Artefak, 2026)
The tatera karau ritual is an important traditional practice among the indigenous community of East Kobalima, Timor Island, East Nusa Tenggara. This ritual is performed in various customary events related to joyful (lia mutin) and mourning (lia metan) ceremonies. This study aims to describe the implementation process of the ritual and analyze the historical values embedded within it. The research employs a qualitative approach using an ethnographic method, with data collected through semi-structured interviews, participatory observation, and document analysis in four traditional villages in East Kobalima. Data were analyzed through stages of data reduction, data display, and verification. The findings reveal that the tatera karau ritual consists of five main stages: tur mutuk (initial deliberation), preparation of ritual equipment, delivery of customary speech, determination of ritual performers, and the core ritual execution. The ritual reflects key historical values, including local wisdom, respect for ancestral spirits, and the reinforcement of communal identity and social cohesion.